Pengaruh Kualitas Pelayanan Dan Lokasi Terhadap Kepuasan Konsumen Pada Resto Agam Kota Metro - Nani Septiana; Suwarto; Juli Adi Fajri (Jurnal Manajemen DIVERSIFIKASI, 2025)
This research aims to determine the effect of service quality and location on consumersatisfaction at the Agam restaurant in Metro City. The type of research used is quantitativeresearch. The instruments used in this research were questionnaires and observations. Dataanalysis was carried out using multiple linear regression. The research results show thatService Quality has a positive and significant influence on consumer satisfaction. Locationhas a positive and significant influence on purchasing decisions. Service Quality andLocation have a positive and significant influence together on consumer satisfaction